BIOMASS-BASED BIOCHAR OBTAINED BY LOW-TEMPERATURE PYROLYSIS IN THE PRESENCE OF METAL OXIDES: PREPARATION, CHARACTERIZATION AND FUTURE APPLICATIONS - Aitbayeva, Aigerim; Uali, Aitolkyn; Shlyapov, Rustam; Vishnyakov, Alexey; Amerkhanova, Shamshiya (National Laboratory Astana, 2022)
Biochar, which is material obtained from biomass by thermochemical decomposition, is an environmentally friendly replacement for carbon materials. Its applications range from heat and energy production, agriculture and livestock farming to analytical chemistry and analysis. This carbon-enriched material can be obtained by using microwave-assisted pyrolysis, hydrothermal carbonization, pyrolysis, and gasification, thus changing the product's structure and properties
Keywords: Type of access: Embargo; Biochar